Synthesis, Characterization and Study of the Biological activity of Some Aldimines Derivatives - Mohamed N. Ibrahim; Hazem K. Al - Deeb (E-Journal of Chemistry)
A number of imines derivatives have been synthesized, they were obtained by condensation of aromatic aldehyde derivatives with primary aromatic amine derivatives. Their structures have been characterised by IR, 1H NMR in addition to the elemental analysis. The biological activity of these imines (which are also known as Schiff bases) were examined against different type of microorganisms and they found to have considerable activity in comparison with the most commonly used antibiotics.